Influence of water invasion on methane adsorption behavior in coal - Wang, Zhaofeng; Su, Weiwei; Tang, Xu; Wu, Jiahao (Elsevier, 2018)
Fluid displacement is the fundamental process for subsurface fossil fuels extraction. Water invasion in coal seams is one of the routinely used stimulation approaches for coal seam methane extraction in underground coal mines. However, how the invading bulk water interacts with adsorbed/gaseous methane in coal is rarely considered even though it is known that moisture presence in coal decreases methane uptake by occupying adsorption sites. Here we study how the invading water interacts with adsorbed/gaseous methane in molded coal under elevated pressures using a custom-designed instrument; the test procedure mimics the real water invasion process in engineering applications. Experimental results demonstrate that invasion water displaces adsorbed methane in nanopores of coal and thus enhances the free gas content. The displacement mechanism can be attributed to capillary effect and preferential flow in a coating mode. It was found that Philip’s sorptivity model can simulate the relationship between displaced methane content and time, and the obtained sorptivity increases with increasing water invasion content and is independent of gas pressure. It was observed that the higher the initial adsorption equilibrium pressure, the larger the displaced methane content, and this can be attributed to the pressure-dependent feature of adsorbed methane density. The higher the invasion water content, the higher the displaced methane content. These experimental results are also applied for optimizing gas drainage borehole arrangement to efficiently drain coal seam gas in underground coal mines. These findings provide a new perspective to understand the interactions between bulk water and methane in coals and pave the way for developing new technologies for methane recovery in coal seams.